KECEMASAN MATEMATIS PESERTA DIDIK PADA FENOMENA LEARNING LOSS PASCA PANDEMI COVID-19 - Hamidah, Zahrah; Nugraheni, Esti Ambar (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractMathematical anxiety is an uncomfortable condition caused by irregular feelings and is usually shown by feeling anxious, worried, and afraid when studying mathematics. This study aims to identify students' mathematical anxiety levels in the learning loss phenomenon after the Covid-19 pandemic. This research is quantitative research with descriptive research methods. The sample of this research is 60 respondents. The subjects of this study were students at the junior high school level located in the Bekasi district. The results of this study indicate that mathematical anxiety in the learning loss phenomenon after the Covid-19 pandemic is in the moderate category with a percentage of 63.3% for class VII and 70% for class VIII. Students' mathematical anxiety on affective aspects which are in moderate indicators is fear and anxiety. Students' mathematical anxiety on the cognitive aspect which is in the moderate indicator is difficult to concentrate. Students' mathematical anxiety in the physiological aspects which are moderate indicators are fast heart palpitations and headaches. Abstrak Kecemasan matematis adalah kondisi tidak enak yang disebabkan oleh perasaan yang tidak beraturan dan biasanya ditujukan dengan rasa gelisah, khawatir, dan takut ketika sedang belajar matematika. Penelitian ini bertujuan untuk mengidentifikasi tingkat kecemasan matematis peserta didik pada feomena learning loss pasca pandemi Covid-19. Penelitian ini merupakan penelitian kuantitatif dengan metode penelitian deskriptif. Sampel penelitian ini berjumlah 60 responden. Subyek penelitian ini adalah peserta didik pada tingkat Sekolah Menengah Pertama (SMP) yang berlokasi di kabupaten bekasi. Hasil penelitian ini menunjukan bahwa kecemasan matematis pada fenomena learning loss pasca pandemi covid-19 berada pada kategori sedang dengan persentase 63.3% untuk kelas VII dan 70% untuk kelas VIII. Kecemasan matematis peserta didik pada aspek afektif yang berada diindikator sedang adalah takut dan gelisah. Kecemasan matematis peserta didik pada aspek kognitif yang berada diindikator sedang adalah sulit konsentrasi. Kecemasan matematis peserta didik pada aspek fisiologis yang berada diindikator sedang adalah jantung berdebar kencang dan sakit kepala.